THE EFFECT OF EXCHANGE RATES AND INTEREST RATES ON THE DEVELOPMENT OF THE INDONESIAN CAPITAL MARKET - Dhenok Darwanti; Evi Okli Lailani; Ahmad Farabi (Journal Of Applied Multidisiplinary Studies, 2025)
This study aims to analyze the effect of the exchange rate and interest rates on the development of the Indonesian capital market, both partially and simultaneously. The study employs a quantitative research approach using secondary time-series data obtained from official financial and economic sources. Data analysis is conducted through descriptive statistical analysis and multiple linear regression techniques to examine the relationship between macroeconomic variables and capital market development. The empirical results indicate that the exchange rate and interest rates simultaneously have a significant effect on the development of the Indonesian capital market. Partially, the rupiah exchange rate against the US dollar has a significant and positive effect, indicating that exchange rate movements play an important role in influencing capital market performance. In contrast, interest rates show a significant and negative effect on capital market development, suggesting that higher interest rates tend to reduce investment activity in the capital market. Furthermore, the Adjusted R² value of 0.7944 demonstrates that 79.44 percent of the variation in the development of the Indonesian capital market can be explained by changes in the exchange rate and interest rates, while the remaining 20.56 percent is influenced by other factors not included in the model. These findings emphasize the importance of maintaining macroeconomic stability, particularly exchange rate management and interest rate policies, to support sustainable growth and strengthen the performance of the Indonesian capital market.